2022
DOI: 10.1007/s10508-022-02315-6
|View full text |Cite
|
Sign up to set email alerts
|

What Does Heterosexuality Mean? Same-Sex Attraction, Behaviors, and Discomfort Among Self-identified Heterosexual Young Adults from Spain

Abstract: Sexuality has been censored by Spanish culture, where legal progress in the form of new policies about sexual diversity rights has not been followed by lower levels of social discrimination. This has affected sexual development across the lifespan for both sexual minorities and heterosexual people who experience their sexuality outside of heteronormativity. However, the literature has regularly excluded the possible consequences of the experience of sexuality within prescriptive categories, particularly in het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…Es decir, las mujeres heterosexuales sintieron mayor malestar al excitarse con la pornografía lésbica, las mujeres lesbianas con la pornografía gay, y las mujeres bisexuales con el material lésbico y el gay. Un tiempo más tarde, se realizó otra investigación con hombres y mujeres heterosexuales (Nebot-Garcia et al, 2022) en la que se comprobó que, pese a identificarse como heterosexuales, algunas personas habían tenido sueños, fantasías y deseos sexuales con personas de su mismo sexo, e incluso algunas habían mantenido relaciones sexuales con ellas. Estas experiencias con el mismo sexo provocaron que las personas heterosexuales sintieran un gran malestar con su propia orientación sexual, sobre todo entre los hombres.…”
Section: Líneas De Investigación Futurasunclassified
See 1 more Smart Citation
“…Es decir, las mujeres heterosexuales sintieron mayor malestar al excitarse con la pornografía lésbica, las mujeres lesbianas con la pornografía gay, y las mujeres bisexuales con el material lésbico y el gay. Un tiempo más tarde, se realizó otra investigación con hombres y mujeres heterosexuales (Nebot-Garcia et al, 2022) en la que se comprobó que, pese a identificarse como heterosexuales, algunas personas habían tenido sueños, fantasías y deseos sexuales con personas de su mismo sexo, e incluso algunas habían mantenido relaciones sexuales con ellas. Estas experiencias con el mismo sexo provocaron que las personas heterosexuales sintieran un gran malestar con su propia orientación sexual, sobre todo entre los hombres.…”
Section: Líneas De Investigación Futurasunclassified
“…That is, heterosexual women felt greater discomfort when aroused by lesbian pornography, lesbian women by gay pornography, and bisexual women by lesbian and gay material. Later, another investigation was carried out with heterosexual men and women (Nebot-Garcia et al, 2022) in which it was found that, despite identifying themselves as heterosexual, some people had had dreams, fantasies and sexual desires with people of the same sex, and some had even had sexual relations with them. These experiences with the same sex caused heterosexual people to feel great discomfort with their sexual orientation, especially men.…”
Section: Future Researchmentioning
confidence: 99%